Teachers' Professional Development Pyramidal Train-To Learn Process - Rafiza, A.R.; Dalwinder, K. (University of Malaya, 2015)
This framework is derived from Bloom's Revised Taxonomy and the stages in Zone of Proximal Teacher Development (ZPTD). Both are relatively new and thus far, there is no study that delineates these abovementioned concepts being used to produce a professional development training framework. There are four stages in this step-by-step professional development framework, which are identified as Train-to-Learn Stage 1 (TL1) to Train-to-Learn Stage 4 (TL4). Although this framework looks hierarchal and the six cognitive processes in the smaller pyramid are presumed to be arranged according to the increasing complexity, they are actually allowed to overlap one another (Anderson et al., 2001). Both these concepts blend very well in producing a four stages training framework which supports the aim of this study which is to introduce a flipped training module for teachers. Copyright@ 2014 University of Malaya all right reserved